The Impact of Universal Mask Use on SARS-COV-2 in Victoria, Australia on the Epidemic Trajectory of COVID-19 - Costantino, Valentina; Raina MacIntyre, Chandini (Frontiers in Public Health, 2021)
Objective(s): to estimate the impact of universal community face mask use in Victoria, Australia with other routine disease control measures in place. Methods: A mathematical modelling study using an age structured deterministic model for Victoria, simulated for 123 days starting on June 1st 2020 until October 1st and incorporating lockdown, contact tracing and case finding, with and without mask use in varied scenarios. The model tested the impact of differing scenarios of universal use of face masks in Victoria, by timing and varying mask effectiveness and uptake. Main outcome: cases and deaths by October 1st 2020 under different scenarios Results: A six-week lockdown with standard control measures but no masks would have resulted in a large resurgence by September following lifting of restrictions. Mask use can substantially reduce the epidemic size, with greater impact if at least 50% of people wear a mask and mask effectiveness is at least 40%. Early mask use averts more cases than mask use implemented close to the peak. No mask use with a 6-week lockdown results in 67,636 cases and 120 deaths by October 1st if no further lockdowns are used. If mask use at 70% uptake commences on July 23rd, this is reduced to 7961 cases and 42 deaths. Conclusion(s): A lockdown and standard control measures may not have controlled the epidemic in Victoria. Mask use can substantially improve epidemic control if uptake is higher than 50% and moderately effective masks are used. Early mask use should be considered in other states if community transmission is present, as this has a greater effect that late mask mandates.